Perceptions of Secondary Level English Teachers on In-Service Teacher Training: A Narrative Inquiry - Timalsina, Sanjaya (Janabhawana Research Journal, 2024)
Teacher training is one of the major components of continuous professional development (CPD) which makes the teacher stay updated and informed regarding the innovative pedagogy and methodology. In-service teacher training is a systematized planning or program through which teachers refresh or upgrade their professional knowledge, skills, and practice. This study aimed to explore the perceptions of secondary-level English teachers on in-service teacher training. The study assessed the perception of the teacher towards in-service teacher training. The study adopted a narrative inquiry methodology. Five participants were selected purposively from Godawari Municipality, Lalitpur. Data were collected through semi-structured in-depth interviews and after transcribing, translating, and classifying them, the data were analyzed thematically. Self-efficacy theory developed by Albert Bandura has been applied to analyze the study. The findings of the study indicated that teachers were positive towards in-service teacher training. They opined that in-service training supported them in their professional development to conduct different hands-on activities effectively in their classrooms, and after this school-based training, they updated themselves with innovative pedagogy and methodology. The teachers demanded regular in-service training based on their needs. Further, teachers focused on ICT-based teacher training rather than theory-laden conventional training but they were not satisfied with the top-down approach of in-service teachers training packages. The study concludes that research needs to be carried out on the impacts on students' performance through teacher training.